2021
DOI: 10.48550/arxiv.2108.13353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Semiorthogonal decomposition of $\mathrm{D}^b(\mathrm{Bun}_2^L)$

Abstract: We study the derived category of coherent sheaves on various versions of moduli space of vector bundles on curves by the Borel-Weil-Bott theory for loop groups and Θ-stratification, and construct a semiorthogonal decomposition with blocks given by symmetric powers of the curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Toward the proof of Conjecture 1.2, Lee and Narasimhan showed that by analyzing the Hecke correspondence, D 𝑏 (𝑋 2 ) is embedded [LN21] when X is nonhyperelliptic and 𝑔 ≥ 16. After this, Tevelev-Torres and Xu-Yau showed that the above building blocks are embedded in D 𝑏 (M(2, 𝐿)) with entirely different approaches [TT21,XY21]. After an early draft of this paper was circulated, very recently, the remaining generation part was proved by Tevelev [Tev23].…”
Section: Semiorthogonal Decompositionmentioning
confidence: 99%
“…Toward the proof of Conjecture 1.2, Lee and Narasimhan showed that by analyzing the Hecke correspondence, D 𝑏 (𝑋 2 ) is embedded [LN21] when X is nonhyperelliptic and 𝑔 ≥ 16. After this, Tevelev-Torres and Xu-Yau showed that the above building blocks are embedded in D 𝑏 (M(2, 𝐿)) with entirely different approaches [TT21,XY21]. After an early draft of this paper was circulated, very recently, the remaining generation part was proved by Tevelev [Tev23].…”
Section: Semiorthogonal Decompositionmentioning
confidence: 99%